Performance and Health Profile of IPB-D1 Chickens Supplemented With Cassava (Manihot Esculenta Crantz) Leaf Extract via Drinking Water: Performa dan Profil Kesehatan Ayam IPB-D1 yang Disuplementasi dengan Ekstrak Daun Singkong (Manihot Esculenta Crantz) melalui Air Minum - Sekar Ayu Hawatama Ramadhani; Ridla, Muhammad; Rita Mutia; Nahrowi; Widya Hermana (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This study evaluated the effects of cassava (Manihot esculenta Crantz) leaves extract (CLE) in drinking water on the performance and health profile of IPB-D1 chickens. Cassava leaves are known to contain bioactive compounds such as flavonoids, tannins, and saponins which have antioxidant and antibacterial properties. These compounds can provide positive effects such as feed efficiency, improving growth performance and health status of chickens by improving the immune system and reducing oxidative stress. Cassava leaves extract acts as a phytogenic additive that can be given in livestock drinking water. This study used 180 IPB-D1 chickens aged 2–8 weeks were randomly assigned to three treatments: CLE0 (control), CLE1 (17 ml/l CLE), and CLE2 (50 ml/l CLE). Parameters observed included growth performance, organ morphometry, hematological profiles, and ileal histology. Data were analyzed using one-way ANOVA and Tukey’s post hoc test (p<0.05). cassava leaves extract supplementation did not adversely affect growth or feed intake. Final body weight and feed conversion ratio (FCR) were not significantly different among the groups. A reduction in leukocyte counts was observed, particularly in the CLE2 group, with a relative increase in heterophils, though values remained within physiological limits. Histological analysis revealed a significant increase in villus surface area in the CLE2 group, followed by CLE1, compared to the control (CLE0), suggesting enhanced intestinal morphology and nutrient absorption potential. Cassava leaves extract can be given in the drinking water of IPB-D1 chickens without disrupting their performance and health profile. These findings indicate that cassava leaves extract can improve gut structure without compromising performance, supporting its application as a safe and beneficial phytogenic additive in poultry diets.